Secure Watermark Image Steganography by Pixel Indicator Based on Randomization - Zena Ahmed; M. Hamid Mohammed Farhan (Journal of Madenat Alelem University College, 2012)
Steganography is the art of hiding the fact that communication is taking place, by hiding information in other information. In this paper have being investigated a method to RGB image steganography based on pixel indicator technique and triple-A algorithm. They uses the same principle of Least Significant Bit (LSB), where the secret is hidden in the least significant bits of the pixels, with more randomization in selection of the number of bits used and the color channels that are used. This randomization is expected to increase the security of the system and also increase the capacity of information. These techniques can be applied to RGB images where each pixel is represented by three bytes (24 bit) to indicate the intensity of red, green, and blue in that pixel. This work showed attractive results especially in the capacity of the data-bits to be hidden with relation to the RGB image pixels. The effective of the proposed stego system has been estimated by Mean Square Error (MSE), Peak Signal to Noise Ratio (PSNR). This paper also illustrates how security has been enhanced using this algorithm.